The assimilation and diffusion of geophysical information systems in the Australian mining sector - Curran, Sharyn Joan (Curtin University, 2015)
Industry contextualization, specific classes of technology and supply relationships have had little impact in understanding technology innovations in Diffusion of Innovations studies. This research uses a qualitative, multiple case study approach to determine the impact of contextualization on the assimilation and diffusion of technological innovation. This research takes a sector wide approach which includes each of the above factors and also critically examines the relationships between these previously unaccounted factors as a determinant of change.